Sero Epidemiology of Camel Brucellosis and its Public Health Significances at Three Selected Districts in Erer Zone, Somali Region (American Journal of Aquaculture and Animal Science, 2024)
Camel brucellosis is an infectious and zoonotic diseases caused by Brucella abortus and Brucella melitensis. A cross-sectional study was conducted on 450 camels from December, 2020 until August, 2021 with the aim of determining sero-prevalence and assessing the associated risk factors for camel brucellosis and its public health significances from purposively selected three districts namely (Fik, Hamaro and Laghida) of Erer zone, Somali Regional state, based on distribution of camel population and sampled using systematic random sampling. The overall sero-prevalence of Brucella in Erer zone was 4.8% (95%, CI: 2.8-6.8). However, the Seroprevalence varied among the different districts with Lagehida 10% (95%, CI: 1.7-18.7), followed by Fik 5.7% (95%, CI: 0.9-10.5) and Hamaro 1.9% (95%, CI: 0.007-0.0522). By computing univariate logistic regression analysis risk factors such as; sex, age, districts, parity, herd sizes, camels that co-exist with other ruminants and reproductive disorder (abortion) (p